Analisis Kinerja Guru Dalam Meningkatkan Dasar Literasi dan Steam Pada Pembelajaran Anak Usia Dini di Yayasan RA Al-Mahir Kec. Percut Sei Tuan Kab. Deli Serdang - Ria Santika; Ahmad Syukri Sitorus; Enny Nazrah Pulungan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Teachers in education play a significant role in the quality of classroom learning. Although teachers are not the only factor influencing educational success, they are an essential component of the overall educational process. This study aims to assist teachers in improving basic literacy and STEAM (Science, Technology, Engineering, Art, and Mathematics) skills in early childhood education at the RA Al-Mahir Foundation. The research seeks to explore the improvement of basic literacy and STEAM in early childhood learning, the stages and implementation of these improvements, and the challenges teachers face in enhancing literacy and STEAM at the foundation. The subjects of this study were classroom teachers and school principals. This research adopts a descriptive qualitative approach, collecting data through observation, interviews, and documentation. The results show that there are two key aspects: first, teacher performance in improving basic literacy and STEAM at the RA Al-Mahir Foundation has been excellent, particularly through the use of methods like reading, singing, and experimental play. Second, the activities aimed at improving literacy and STEAM have been effective and well implemented. The learning process at the RA Al-Mahir Foundation is running smoothly, with teachers successfully increasing children's interest in literacy and STEAM. This includes improved reading interest, focus during reading and experimental activities, politeness in the learning process, and good behavior, all contributing to a positive learning environment.